Geochemical modelling of the effects of a proposed uranium tailings pond on groundwater quality. Technical article - Brindha, Karthikeyan; Elango, L. (Springer, 2014)
The impact of a proposed uranium tailings pond on groundwater quality was assessed by geochemical modelling. Groundwater samples were collected from six dug wells in the Nalgonda district, Andhra Pradesh, in southern India, once every 2 months from March 2008 to January 2010, and analysed for calcium, magnesium, sodium, potassium, chloride, sulphate, carbonate, bicarbonate, and uranium. Prediction of groundwater quality was carried out for 100 years using PHREEQC to assess the effects of infiltration of water from the proposed tailings pond. The sensitivity of the model for variations in porosity, hydraulic gradient, hydraulic conductivity, and concentration of uranium in the tailings was evaluated. Geochemical modelling predicts that if the chemical composition of the tailings water is maintained at about the expected mean concentrations, and an appropriate liner is installed with an infiltration rate B1.0 9 10-9 m/s, the concentration of solutes in the groundwater will be increased from present background levels for a down-gradient distance of up to 500 m for the anticipated life of the mine, i.e. 16 years. The concentration of ions in groundwater would exceed background concentrations for up to 100 m at the end of 100 years. This study was used to predict the optimum chemical composition for the tailings and the extent, in terms of time and distance, that the groundwater concentration of various ions would be increased by infiltration of wastes from the tailings pond.